NATIONAL EXPERIENCE OF CREATING AND IMPLEMENTING MEDICAL STANDARDS IN CASE EVIDENCE APPEARS «LATER» (DURING THE COVID-19 CORONAVIRUS DISEASE PANDEMIC) - Dyachuk, Dmytro D; Stepanenko, Alla V; Lishchyshyna, Olena M; Zyukov, Oleg L; Oshivalova, Olena O (Wiadomości lekarskie (1960), 2022)
The aim: Identification of methodological processes to accelerate the development of clinical guidelines in an emergency situation (in particular, coronavirus disease COVID-19), analysis of the practice of implementing clinical guidelines and clinical pathway.OBJECTIVEThe aim: Identification of methodological processes to accelerate the development of clinical guidelines in an emergency situation (in particular, coronavirus disease COVID-19), analysis of the practice of implementing clinical guidelines and clinical pathway.Materials and methods: The processes of developing COVID-19 clinical guidelines are described on the websites of the developers. Implementing the patient's own clinical pathway. Survey of 117 health professionals involved in medical care at COVID-19 on management information. A retrospective pragmatic study of organizational and clinical aspects of medical care for 9,259 patients over 18 years with COVID-19 from March 18, 2020 to March 31, 2021.PATIENTS AND METHODSMaterials and methods: The processes of developing COVID-19 clinical guidelines are described on the websites of the developers. Implementing the patient's own clinical pathway. Survey of 117 health professionals involved in medical care at COVID-19 on management information. A retrospective pragmatic study of organizational and clinical aspects of medical care for 9,259 patients over 18 years with COVID-19 from March 18, 2020 to March 31, 2021.Results: Acceleration of the methodology of clinical guidelines, changes in legislation have contributed to the improvement of medical care for patients with COVID-19. Clinical pathway (CPw) professionals surveyed: 88.2% satisfied with the structure of CPw, 91.0% were in favor of local instructions and explanations, templates of registration forms, 72.7% needed on-the-job training, 78.1% needed training on medical features, 74.5% noted the positive impact of remote interaction, 61.6% required standard operating procedures. 9259 patients with suspected COVID-19 confirmed PCR in 55.2%. Among those checked, 31.2% of chest computed tomography confirmed pneumonia in 95.7% of CT; 9.3% were hospitalized; fatalities 5.5% of hospitalized or 0.5% of verified.RESULTSResults: Acceleration of the methodology of clinical guidelines, changes in legislation have contributed to the improvement of medical care for patients with COVID-19. Clinical pathway (CPw) professionals surveyed: 88.2% satisfied with the structure of CPw, 91.0% were in favor of local instructions and explanations, templates of registration forms, 72.7% needed on-the-job training, 78.1% needed training on medical features, 74.5% noted the positive impact of remote interaction, 61.6% required standard operating procedures. 9259 patients with suspected COVID-19 confirmed PCR in 55.2%. Among those checked, 31.2% of chest computed tomography confirmed pneumonia in 95.7% of CT; 9.3% were hospitalized; fatalities 5.5% of hospitalized or 0.5% of verified.Conclusions: Changes in the methodology of clinical guidelines, changes in legislation, education based on clinical guidelines have contributed to improving the results of management in COVID-19.CONCLUSIONConclusions: Changes in the methodology of clinical guidelines, changes in legislation, education based on clinical guidelines have contributed to improving the results of management in COVID-19.